The installation of Inkosi ya Makosi Gomani III - Nurse, G. T. (International Library of African Music, 1966)
In this historical context the installation was of greater interest than might, to some of the visitors present at it, have been apparent. For one thing, it was only the second time this century that a Maseko chief of the direct fine had ritually assumed his inheritance; for another, it represented a melding of the authority of a new African state with one of the traditions that had produced it. Not the least curious aspects were the use in the ritual of a Bantu language other than that commonly spoken by the people, and the concomitant resurgence of the musical and poetic patterns characteristic of that language. Thirty years ago Ngoni, described by the early European settlers as Zulu but more properly a form of Swazi, was still spoken by the old people. Today, despite the numbers of young men who have been to South Africa and come in contact with one or other of the Nguni languages there, it persists only in the songs and praises; and, as might be expected where the communication is by ear and is not written down, and where the meaning is only remotely comprehended, has undergone considerable modification.
Keywords: Ngoni (African people); Rites and ceremonies; History; Ethnomusicology; Bantu languages; African Music